Impact of Media on Mental Health during COVID-19 Period: A Bangladesh Perspective (Journal of Chittagong Medical College Teachers' Association, 2025)
Background: The COVID-19 outbreak has provided an opportunity to examine the psychological impact of media coverage during a pandemic. This study aimed to understand the media's role in such a situation, especially in the context of a developing country like Bangladesh.Materials and methods: This descriptive, cross-sectional, web-based survey was conducted in June and July 2020 among the Bangladeshi people. The Google form included sociodemographic, media consumption, and mental status questions from the Bangla Validated Depression, Anxiety and Stress Scale-21 (DASS-21 scale). The results were analyzed with SPSS 26.Results: Among 536 responses, younger demographics scored higher in all domains of the DASS-21 scale. Social media was more preferred for obtaining information (43.0%) or for recreational purposes (43.8%). 81.3% of respondents believed that media campaign had a significant negative or mixed effect on their mental health. Whereas 56.1% of respondents reported that they were almost always exposed to information about COVID-19. Responders with increased screen time also displayed comparatively higher DASS-21 scores.  Conclusion: Exposure to COVID-19-related information in the media may have a distressing effect on mental health, especially among the younger population. Necessary interventions are required to minimize this negative impact in the future public health crisis.   JCMCTA 2024 ; 35 (1) : 52-57